Compositions containing novel polyesters

Thermoplastic polymerization is solved by developing a biodegradable composition containing 2,5-furandicarboxylic acid polyester and polyhydroxyalkanoate or aliphatic-aromatic diacid glycol polyester, combined with fillers and plant fibers. The toughness and productivity problems in material materials achieve high performance and high barrier properties polymers, suitable for a variety of application fields.

CN119192794APending Publication Date: 2024-12-27NOVAMONT SPA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411307286.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2016-04-20
Filing Date
2017-04-20
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

In thermoplastic polymer materials, especially in packaging films and molded products, it is difficult to find products with good toughness, deformability and high load tolerance, while ensuring high productivity and reducing deformation tendencies in the mold cooling stage.

Method used

A biodegradable composition has been developed, comprising 20-60% polyester containing 2,5-furandicarboxylic acid and 20-70% polyhydroxyalkanoate or aliphatic-aromatic diacid diol Polyester, combined with 0-50% filler and 0-30% plant fiber, optimizes the mechanical and processing properties of the polymer, and improves the barrier properties of oxygen and carbon dioxide through specific formulation and process conditions.

Benefits of technology

It achieves high performance and excellent processability in use, especially in terms of mechanical properties and barrier properties. It is suitable for the preparation of high-quality films, fibers, nonwoven fabrics, molding, thermoforming and expanded products, suitable for use In disposable tableware, food packaging and microwave grilling containers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005049628930000281
    Figure BDA0005049628930000281
  • Figure BDA0005049628930000291
    Figure BDA0005049628930000291
Patent Text Reader

Abstract

The present invention relates to biodegradable compositions containing at least a polyester containing 2, 5-furandicarboxylic acid and at least a polymer selected from the group consisting of polyhydroxyalkanoates and / or aliphatic and / or aliphatic-aromatic diacid diol polyesters, which are particularly suitable for the manufacture of mass-produced articles, such as, for example, articles of manufacture. The articles are characterized by excellent mechanical properties relating to high barrier properties against oxygen and carbon dioxide.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This invention patent application is a divisional application of the invention patent application with application number 2017800329612, application date April 20, 2017, and invention name “Composition containing new polyester”.

[0002] describe

[0003] The present invention relates to a biodegradable composition comprising at least a polyester containing 2,5-furandicarboxylic acid and at least a polymer selected from polyhydroxyalkanoates and / or aliphatic and / or aliphatic-aromatic diacid diol polyesters, characterized by remarkable processability and characterized in that it can be processed into products such as films, fibers, nonwoven fabrics, sheets, molded, injection-molded, thermoformed, blow-molded and expanded articles, said articles being characterized by excellent mechanical properties in conjunction with high barrier properties against oxygen and carbon dioxide.

[0004] Over time, polymer materials have become increasingly popular due to their versatility, the fact that they can be easily processed and their low cost.

[0005] For example, among thermoplastic polymer materials, the development of new compositions containing polyesters has acquired particular importance. Polymeric materials of this type have in fact found major applications in the fields of fibers, molding, injection and blow molding and film products.

[0006] However, the increasing use of polymer materials in technologically progressive fields of application does require the continuous development of new materials which can ensure increasingly high performance during use.

[0007] For example, in the field of thermoplastic polyesters for the preparation of packaging films, one of the great difficulties is to obtain products characterized by a good balance between toughness and deformability and the ability to withstand high loads.

[0008] On the other hand, in the field of moulded articles, one of the greatest difficulties is to ensure high production rates, minimising the tendency of the manufactured articles to deform, for example during the mould cooling phase, known as mould shrinkage.

[0009] The problem addressed by the present invention is therefore to find novel biodegradable compositions comprising at least a polyester containing 2,5-furandicarboxylic acid and at least a polymer chosen from polyhydroxyalkanoates and / or aliphatic and / or aliphatic-aromatic diacid diol polyesters, which ensure high performance of the products obtained using it during use, in particular excellent processability and mechanical properties, together with high barrier properties against oxygen and carbon dioxide.

[0010] Starting from this problem, it has now been found, surprisingly, that compositions having the properties mentioned above can be obtained.

[0011] In particular, the present invention relates to the following aspects:

[0012] Item 1. A biodegradable composition, relative to the total amount of components i.-iv., comprising:

[0013] i) 20-60 wt. % of at least one biodegradable polyester;

[0014] ii) 20-70% by weight of at least one biodegradable polymer other than the polyester i., selected from polyhydroxyalkanoates and / or aliphatic and / or aliphatic-aromatic diacid diol polyesters other than the polyester i., and mixtures thereof;

[0015] iii) 0-50 wt. % of at least one filler;

[0016] iv) 0-30 wt.% vegetable fibers.

[0017] The biodegradable polyester i. comprises:

[0018] a) a dicarboxylic acid component, comprising, relative to the total dicarboxylic acid component:

[0019] a1) 85 to 65 mol % of units derived from 2,5-furandicarboxylic acid or an ester thereof;

[0020] a2) 15 to 35 mol % of units derived from at least one saturated dicarboxylic acid selected from adipic acid, azelaic acid, succinic acid, sebacic acid, brassylic acid or esters or derivatives thereof, preferably azelaic acid;

[0021] a3) 0 to 15 mol % of units derived from at least one aliphatic saturated dicarboxylic acid which is not a saturated dicarboxylic acid in component a2 and is preferably selected from saturated C2-C 24 , preferably C4-C 13 , more preferably C4-C 11 A dicarboxylic acid, or an ester thereof;

[0022] a4) 0 to 5 mol % of units derived from at least one unsaturated aliphatic dicarboxylic acid or an ester thereof;

[0023] b) a diol component, comprising, relative to the total diol component:

[0024] b1) 95 to 100 mol % of units derived from 1,2-ethylene glycol;

[0025] b2) 0 to 5 mol % derived from at least one saturated aliphatic diol other than 1,2-ethylene glycol

[0026] Alcohol units;

[0027] b3) 0 to 5 mol % of units derived from at least one unsaturated aliphatic diol.

[0028] Item 2. A biodegradable composition, relative to the total amount of components i.-iv., comprising:

[0029] i) 20-60% by weight of at least one biodegradable polyester i.;

[0030] ii) 20-70% by weight of at least one polyhydroxyalkanoate;

[0031] iii) 0-50 wt. % of at least one filler;

[0032] iv) 0-30 wt.% vegetable fibers.

[0033] Item 3. A biodegradable composition, relative to the total amount of components i.-iv., comprising:

[0034] i) 20-60% by weight of at least one biodegradable polyester i.;

[0035] ii) 20 to 70% by weight of at least one aliphatic diacid diol polyester;

[0036] iii) 0-50 wt. % of at least one filler;

[0037] iv) 0-30 wt.% vegetable fibers.

[0038] Item 4. A biodegradable composition, relative to the total amount of components i.-iv., comprising:

[0039] v) 20-60% by weight, preferably 25-55% by weight, more preferably 25-50% by weight of at least one biodegradable polyester i.;

[0040] vi) 20 to 70% by weight, preferably 25 to 65% by weight, of at least one aliphatic-aromatic diacid diol polyester;

[0041] vii) 0-50 wt %, preferably 3-45 wt %, more preferably 5-40 wt % of at least one filler;

[0042] viii) 0-30 wt.% vegetable fibers.

[0043] Item 5. A biodegradable composition according to any one of items 1-4, characterized in that the relative humidity is less than 20 (cm 3 ×mm) / (m 2 × 24h × bar) against oxygen permeation barrier.

[0044] Item 6. A biodegradable composition according to any one of items 1-4, characterized in that the relative humidity is less than 45 (cm 3 ×mm) / (m 2 × 24h × bar) against the permeation barrier of carbon dioxide.

[0045] Item 7. A biodegradable composition according to any one of items 1 to 4, characterized in that the relative humidity is less than 80 (g × 30 μm) / (m 2 × 24h) permeation barrier against water vapor transmission.

[0046] Item 8. The biodegradable composition according to any one of Items 1 to 4, characterized by a G' modulus value higher than 40 MPa at 70°C obtained via dynamic mechanical-torque analysis.

[0047] Item 9. Films, fibers, nonwoven fabrics, sheets, molded, thermoformed, blown, expanded and laminated products comprising the composition according to any one of Items 1 to 4.

[0048] Item 10. An injection molded article comprising the composition according to any one of Items 1-4.

[0049] Item 11. The injection molded article according to Item 10, suitable for preparing disposable cutlery, plates and cups, rigid containers, capsules for delivering beverages, preferably hot beverages, caps and lids, and food packaging that can be heated in conventional and microwave ovens.

[0050] The present invention relates to a biodegradable composition comprising, relative to the total amount of components i. to iv.:

[0051] i) 20-60% by weight, preferably 25-55% by weight, more preferably 25-50% by weight of at least one biodegradable polyester;

[0052] ii) 20-70% by weight, preferably 25-65% by weight, of at least one biodegradable polymer other than the polyester i., selected from polyhydroxyalkanoates and / or aliphatic and / or aliphatic-aromatic diacid diol polyesters other than the polyester i., and mixtures thereof;

[0053] iii) 0-50 wt %, preferably 3-45 wt %, more preferably 5-40 wt % of at least one filler;

[0054] iv) 0-30 wt.% vegetable fibers.

[0055] wherein the biodegradable aliphatic-aromatic polyester i. comprises:

[0056] a) a dicarboxylic acid component, comprising, relative to the total dicarboxylic acid component:

[0057] a1) 85-65 mol %, preferably 80-70 mol % derived from 2,5-furandicarboxylic acid

[0058] or units of esters thereof;

[0059] a2) 15-35 mol %, preferably 20-30 mol %, of units derived from at least one saturated dicarboxylic acid selected from adipic acid, azelaic acid, succinic acid, sebacic acid, brassylic acid or esters or derivatives thereof, preferably azelaic acid;

[0060] a3) 0 to 15 mol %, preferably 0 to 10 mol % of units derived from at least one aliphatic saturated dicarboxylic acid which is not a saturated dicarboxylic acid in component a2 and is preferably selected from saturated C2-C 24 , preferably C4-C 13 , more preferably C4-C 11 A dicarboxylic acid, or an ester thereof;

[0061] a4) 0-5 mol%, preferably 0.1-1 mol%, more preferably 0.2-0.7 mol%

[0062] Units derived from at least one unsaturated aliphatic dicarboxylic acid or an ester thereof;

[0063] b) a diol component, comprising, relative to the total diol component:

[0064] b1) 95 to 100 mol % of units derived from 1,2-ethylene glycol;

[0065] b2) 0 to 5 mol % derived from at least one saturated aliphatic diol other than 1,2-ethylene glycol

[0066] Alcohol units;

[0067] b3) 0 to 5 mol %, preferably 0 to 3 mol %, of units derived from at least one unsaturated aliphatic diol.

[0068] The saturated aliphatic dicarboxylic acids which are not saturated dicarboxylic acids in component a2 (component a3 of the polyester i.) are preferably selected from saturated C2-C 24 , preferably C4-C 13 , more preferably C4-C 11 Dicarboxylic acids, their C1-C 24 , preferably C1-C4 alkyl esters, their salts and mixtures thereof. The unsaturated aliphatic dicarboxylic acid (component a4 of the polyester i.) is preferably selected from itaconic acid, fumaric acid, 4-methylenepimelane dicarboxylic acid, 3,4-bis(methylene)azelaic acid, 5-methyleneazelaic acid, their C1-C 24, preferably C1-C4 alkyl esters, their salts and mixtures thereof. In a preferred embodiment of the present invention, the unsaturated aliphatic dicarboxylic acid comprises at least 50 mol%, preferably greater than 60 mol%, more preferably greater than 65 mol% itaconic acid, wherein the C1-C4 alkyl esters 24 , preferably a mixture of C1-C4 esters. More preferably, the unsaturated aliphatic dicarboxylic acid comprises itaconic acid.

[0069] As regards the saturated aliphatic diols which are not 1,2-ethanediol (component b2 of the polyester i.), they are preferably selected from 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,4-cyclohexanedimethanol, neopentyl glycol, 2-methyl-1,3-propanediol, dianhydrosorbitol, dianhydromannitol, dianhydroiditol, cyclohexanediol, cyclohexanemethanediol, dialkylene glycols and polyalkylene glycols having a molecular weight of 100 to 4000, for example polyethylene glycol, polypropylene glycol and mixtures thereof. Preferably, the diol component other than 1,2-ethanediol comprises at least 50 mol% of one or more diols selected from 1,3-propylene glycol or 1,4-butanediol. More preferably, the diol component comprises or consists of 1,4-butanediol.

[0070] As for the unsaturated aliphatic diols (component b3) of the polyester i., they are preferably selected from cis-2-butene-1,4-diol, trans-2-butene-1,4-diol, 2-butyne-1,4-diol, cis-2-pentene-1,5-diol, trans-2-pentene-1,5-diol, 2-pentyne-1,5-diol, cis-2-hexene-1,6-diol, trans-2-hexene-1,6-diol, 2-hexyne-1,6-diol, cis-3-hexene-1,6-diol, trans-3-hexene-1,6-diol, 3-hexyne-1,6-diol.

[0071] In addition to the dicarboxylic acid component and the diol component, the polyester i. of the composition according to the invention preferably comprises repeating units derived from at least one hydroxy acid in an amount of 0 to 49 mol %, preferably 0 to 30 mol %, relative to the total moles of the dicarboxylic acid component. Examples of suitable hydroxy acids are glycolic acid, hydroxybutyric acid, hydroxycaproic acid, hydroxyvaleric acid, 7-hydroxyheptanoic acid, 8-hydroxycaproic acid or 9-hydroxynonanoic acid, lactic acid or lactide. The hydroxy acids can be incorporated into the chain as such or can also be reacted beforehand with a diacid or a diol.

[0072] Long molecules containing two functional groups (including functional groups not in terminal positions) may also be present in an amount not exceeding 10 mol % relative to the total moles of the dicarboxylic acid component. Examples are dimer acids, ricinoleic acid and acids into which epoxy groups are introduced, including polyethylene oxides having a molecular weight of 200-10,000.

[0073] Diamines, amino acids and amino alcohols may also be present in a percentage of up to 30 mol %, relative to the total moles of the dicarboxylic acid component.

[0074] During the preparation of the polyester i. of the composition according to the invention, one or more molecules containing multiple functional groups may also be advantageously added in an amount of 0.1 to 3 mol % relative to the total moles of the dicarboxylic acid component (including any hydroxy acids) in order to obtain branched products. Examples of these molecules are glycerol, pentaerythritol, trimethylolpropane, citric acid, dipentaerythritol, triglycerides, polyglycerols.

[0075] The molecular weight Mn of the polyester i. of the composition according to the invention is preferably ≥ 20 000, more preferably ≥ 40 000. As for the polydispersity index Mw / Mn of the molecular weight, it is instead preferably 1.5-10, more preferably 1.6-5, even more preferably 1.8-2.7.

[0076] The molecular weights Mn and Mw can be measured by gel permeation chromatography (GPC). The determination can be carried out using a chromatography system maintained at 40°C, using a set of three columns in series (5 μm particle diameter and unit, Units and The HPLC-MS / MS was carried out using a porosity of 1000 nm (1000 Å), a refractive index detector, hexafluoroisopropanol (HFIP) as eluent (flow rate 1 ml / min), and poly(methyl methacrylate) as reference standard.

[0077] Preferably, the polyester i. of the composition according to the invention has an intrinsic viscosity greater than 0.3 dl / g, preferably 0.3-2 dl / g, more preferably 0.4-1.2 dl / g (measured using an Ubbelohde viscometer in a 1:1 v / v dichloromethane-trifluoroacetic acid solution at a concentration of 0.5 g / dl at 25°C).

[0078] The polyester i. has a glass transition temperature (Tg) of 5°C to 60°C as measured by differential scanning calorimetry.

[0079] The polyester i. of the composition according to the invention is biodegradable. In the sense of the present invention, a so-called biodegradable polyester is a biodegradable polyester according to standard EN 13432.

[0080] The polyesters i. of the composition according to the invention can be synthesized according to any of the methods known in the prior art. In particular, they can be advantageously obtained by polycondensation.

[0081] Advantageously, the synthesis method can be carried out in the presence of a suitable catalyst. As suitable catalysts, mention may be made of organometallic compounds such as tin, such as stannic acid derivatives, titanium compounds, such as orthobutyl titanate, aluminum compounds, such as triisopropyl Al, and compounds of antimony, zinc and zirconium, and mixtures thereof.

[0082] As regards the biodegradable polymers other than polyester i. (component ii.), they are selected from polyhydroxyalkanoates and / or aliphatic and / or aliphatic-aromatic diacid diol polyesters other than polyester i., and mixtures thereof.

[0083] As for the polyhydroxyalkanoates, they are preferably chosen from lactic acid polyesters, poly-ε-caprolactone, polyhydroxybutyrate, polyhydroxybutyrate-valerate, polyhydroxybutyrate-propionate, polyhydroxybutyrate-hexanoate, polyhydroxybutyrate-decanoate, polyhydroxybutyrate-dodecanoate, polyhydroxybutyrate-hexadecanoate, polyhydroxybutyrate-octadecanoate, poly-3-hydroxybutyrate-4-hydroxybutyrate. Preferably, the polyhydroxyalkanoates in the composition comprise at least 80% by weight of one or more polyesters of lactic acid. In a preferred embodiment, the lactic acid polyester is chosen from poly-L-lactic acid, poly-D-lactic acid, poly-DL-lactic acid stereocomplexes, copolymers containing more than 50 mol % of the lactic acid polyester or mixtures thereof. Particularly preferred are those containing at least 95% by weight of repeating units derived from L-lactic acid or D-lactic acid or a combination thereof, having a molecular weight Mw greater than 50,000 and 50-500 Pa.s, preferably 100-300 Pa.s (according to ASTM standard D3835 at T = 190 ° C, shear rate = 1000 s -1 , D=1 mm, L / D=10) of lactic acid polyester.

[0084] In a particularly preferred embodiment of the invention, the lactic acid polyester comprises at least 95% by weight of units derived from L-lactic acid, ≤5% of repeating units derived from D-lactic acid, has a melting point of 135-170° C., a glass transition temperature (Tg) of 55-65° C. and an MFR of 1-50 g / 10 min (measured according to standard ISO 1133-1 at 190° C. and 2.16 kg). Commercial examples of lactic acid polyesters having these properties are, for example, Ingeo TM Products manufactured by Biopolymer 4043D, 3251D and 6202D.

[0085] As regards the diacid diol polyesters which are not polyesters i. (component ii.), they are preferably selected from polyesters comprising:

[0086] a) a dicarboxylic acid component, comprising, relative to the total dicarboxylic acid component:

[0087] a11) 0-40 mol %, preferably 0-20 mol % of one or more aromatic diacids, their esters or salts;

[0088] a12) 60-100 mol %, preferably 80-100 mol % of one or more aliphatic diacids, their esters or salts;

[0089] or

[0090] a21) 40-95 mol %, preferably 45-80 mol % of one or more aromatic diacids, their esters or salts;

[0091] a22) 5-60 mol %, preferably 20-55 mol % of one or more aliphatic diacids, their esters or salts;

[0092] b) a diol component comprising derivative units relative to the total diol component:

[0093] b1) 95 to 100 mol % of units derived from at least one saturated aliphatic diol;

[0094] b2) 0 to 5 mol % of units derived from at least one unsaturated aliphatic diol.

[0095] Preferably, the aromatic dicarboxylic acids, saturated aliphatic dicarboxylic acids, unsaturated aliphatic dicarboxylic acids, saturated aliphatic diols and unsaturated aliphatic diols of the polyester are selected from those described above for the polyesters according to the invention (component i.). More preferably, the diacid diol polyesters which are not polyesters i. are selected from block or random copolymers of the poly(alkylene alkylate), poly(alkylene terephthalate-co-alkylene alkylate) or poly(2,5-furandicarboxylic acid alkylene ester-co-alkylene alkylate) type. Preferred examples of diacid diol polyesters other than polyester i. are selected from the group consisting of: poly(1,4-butylene succinate), poly(1,2-ethylene succinate), poly(1,4-butylene adipate), poly(1,2-ethylene adipate), poly(1,4-butylene azelaic acid), poly(1,2-ethylene azelaic acid), poly(1,4-butylene sebacate), poly(1,2-ethylene sebacate), poly(1,2-ethylene succinate-co-1,4-butylene succinate), poly(1,2-ethylene adipate-co-1,4-butylene adipate), poly( 1,2-ethylene glycol azelaic acid-co-1,4-butylene glycol azelaic acid), poly(1,2-ethylene glycol sebacate-co-1,4-butylene glycol sebacate), poly(1,2-ethylene glycol succinate-co-1,4-butylene glycol adipate), poly(1,2-ethylene glycol succinate-co-1,4-butylene glycol azelaic acid), poly(1,2-ethylene glycol succinate-co-1,4-butylene glycol sebacate), poly(1,2-ethylene glycol adipate-co-1,4-butylene glycol succinate), poly(1,2-ethylene glycol adipate-co-1,4-butylene glycol azelaic acid). Poly(1,2-ethylene adipate-co-1,4-butylene sebacate), Poly(1,2-ethylene azelaic acid-co-1,4-butylene succinate), Poly(1,2-ethylene azelaic acid-co-1,4-butylene adipate), Poly(1,2-ethylene azelaic acid-co-1,4-butylene sebacate), Poly(1,2-ethylene sebacate-co-1,4-butylene succinate), Poly(1,2-ethylene sebacate-co-1,4-butylene adipate), Poly(1,2-ethylene sebacate-co-1,4-butylene succinate), Poly(1,2-ethylene sebacate-co-1,4-butylene adipate), Poly(1,2-ethylene sebacate-co- 1,4-butylene diacid), poly(1,4-butylene adipate-co-1,4-butylene succinate), poly(1,4-butylene azelaic acid-co-1,4-butylene succinate), poly(1,4-butylene sebacate-co-1,4-butylene succinate), poly(1,4-butylene succinate-co-1,4-butylene adipate-co-1,4-butylene azelaic acid), poly(1,4-butylene adipate-co-1,4-butylene terephthalate), poly(1,4-butylene sebacate-co-1,4-butylene terephthalate).4-butylene glycol ester), poly(1,4-butylene glycol azelaate-co-1,4-butylene glycol terephthalate), poly(1,4-butylene glycol brazylate-co-1,4-butylene glycol terephthalate), poly(1,4-butylene glycol succinate-co-1,4-butylene glycol terephthalate), poly(1,4-butylene glycol adipate-co-1,4-butylene glycol sebacate-co-1,4-butylene glycol terephthalate), poly(1,4-butylene glycol azelaate-co-1,4-butylene glycol sebacate-co-1,4-butylene glycol terephthalate), poly(1,4-butylene glycol adipate-co-1,4-butylene glycol azelaic acid-co-1,4-butylene glycol terephthalate), poly (1,4-butylene succinate-co-1,4-butylene sebacate-co-1,4-butylene terephthalate), poly(1,4-butylene adipate-co-1,4-butylene succinate-co-1,4-butylene terephthalate), poly(1,4-butylene azelaic acid-co-1,4-butylene succinate-co-1,4-butylene terephthalate), poly(1,4-butylene adipate-co-1,4-butylene 2,5-furandicarboxylate), poly(1,4-butylene sebacate-co-1,4-butylene 2,5-furandicarboxylate), poly(1,4-butylene azelaic acid-co-1,4-butylene 2,5-furandicarboxylate), Poly(1,4-butylene brazilate-co-1,4-butylene 2,5-furandicarboxylate), poly(1,4-butylene succinate-co-1,4-butylene 2,5-furandicarboxylate), poly(1,4-butylene adipate-co-1,4-butylene sebacate-co-1,4-butylene 2,5-furandicarboxylate), poly(1,4-butylene azelaic acid-co-1,4-butylene sebacate-co-1,4-butylene 2,5-furandicarboxylate), poly(1,4-butylene adipate-co-1,4-butylene azelaic acid-co-1,4-butylene 2,5-furandicarboxylate), poly(1,4-butylene succinate-co-1,4-butylene sebacate-co-1,4-butylene 2,5-furandicarboxylate ,4-butylene glycol ester-co-2,5-furandicarboxylic acid 1,4-butylene glycol ester), poly(1,4-butylene glycol adipate-co-1,4-butylene glycol succinate-co-2,5-furandicarboxylic acid 1,4-butylene glycol ester), poly(1,4-butylene glycol azelaic acid-co-1,4-butylene glycol succinate-co-2,5-furandicarboxylic acid 1,4-butylene glycol ester), poly(1,2-ethylene adipate-co-2,5-furandicarboxylic acid 1,2-ethylene glycol ester), poly(1,2-ethylene sebacate-co-2,5-furandicarboxylic acid 1,2-ethylene glycol ester), poly(1,2-ethylene azelaic acid-co-2,5-furandicarboxylic acid 1,2-ethylene glycol ester), poly(1,4-butylene glycol ester), poly(1,4-butylene glycol ester), poly(1,4-butylene glycol ester), poly(1,4-butylene glycol ester), poly(1,4-butylene glycol ester), poly(1,4-butylene glycol ester), poly(1,4-butylene glycol ester), poly(1,4-butylene glycol ester).2-ethylene glycol ester-co-2,5-furan dicarboxylic acid 1,2-ethylene glycol ester), poly(1,2-ethylene glycol succinate-co-2,5-furan dicarboxylic acid 1,2-ethylene glycol ester), poly(1,2-ethylene glycol adipate-co-1,2-ethylene glycol sebacate-co-2,5-furan dicarboxylic acid 1,2-ethylene glycol ester), poly(1,2-ethylene glycol azelaic acid-co-1,2-ethylene glycol sebacate-co-2,5-furan dicarboxylic acid 1,2-ethylene glycol ester), poly(1,2-ethylene glycol adipate-co-1,2-ethylene glycol azelaic acid-co-1,2-ethylene glycol ester). 1,2-ethylene glycol ester-co-2,5-furandicarboxylic acid 1,2-ethylene glycol ester), poly(1,2-ethylene glycol succinate-co-1,2-ethylene glycol sebacate-co-2,5-furandicarboxylic acid 1,2-ethylene glycol ester), poly(1,2-ethylene glycol adipate-co-1,2-ethylene glycol succinate-co-2,5-furandicarboxylic acid 1,2-ethylene glycol ester), poly(1,2-ethylene glycol azelaic acid-co-1,2-ethylene glycol succinate-co-2,5-furandicarboxylic acid 1,2-ethylene glycol ester), their copolymers and mixtures.

[0096] In another preferred embodiment of the present invention, the diacid-diol polyester which is not a polyester i. is selected from:

[0097] (A) A polyester comprising repeating units derived from an aromatic dicarboxylic acid of the phthalic acid type, preferably terephthalic acid, an aliphatic dicarboxylic acid and an aliphatic diol (AAPE-A), characterized in that the aromatic unit content is 35-60 mol %, preferably 40-55 mol %, relative to the total moles of the dicarboxylic acid components. The AAPE-A polyester is preferably selected from the group consisting of poly(1,4-butylene adipate-co-1,4-butylene terephthalate), poly(1,4-butylene sebacate-co-1,4-butylene terephthalate), poly(1,4-butylene azelaic acid-co-1,4-butylene terephthalate), poly(1,4-butylene brassyl acid-co-1,4-butylene terephthalate), poly(1,4-butylene succinate-co-1,4-butylene terephthalate), poly(1,4-butylene adipate-co-1,4-butylene sebacate-co-1,4-butylene terephthalate), poly(1,4-butylene azelaic acid-co-1,4-butylene terephthalate). 4-butylene glycol ester-co-1,4-butylene sebacate-co-1,4-butylene terephthalate), poly(1,4-butylene adipate-co-1,4-butylene azelaic acid-co-1,4-butylene terephthalate), poly(1,4-butylene succinate-co-1,4-butylene sebacate-co-1,4-butylene terephthalate), poly(1,4-butylene adipate-co-1,4-butylene succinate-co-1,4-butylene terephthalate), poly(1,4-butylene azelaic acid-co-1,4-butylene succinate-co-1,4-butylene terephthalate).

[0098] (B) a polyester (AAPE-B) comprising repeating units derived from a heterocyclic dicarboxylic acid aromatic compound, preferably 2,5-furandicarboxylic acid, an aliphatic dicarboxylic acid and an aliphatic diol, characterized in that the aromatic unit content is 50-80 mol %, preferably 60-75 mol %, relative to the total moles of the dicarboxylic acid component. The AAPE-B polyester is preferably selected from the group consisting of poly(1,4-butylene adipate-co-1,4-butylene 2,5-furandicarboxylate), poly(1,4-butylene sebacate-co-1,4-butylene 2,5-furandicarboxylate), poly(1,4-butylene azelaic acid-co-1,4-butylene 2,5-furandicarboxylate), poly(1,4-butylene brassylate-co-1,4-butylene 2,5-furandicarboxylate), poly(1,4-butylene succinate-co-1,4-butylene 2,5-furandicarboxylate), poly(1,4-butylene adipate-co-1,4-butylene sebacate-co-1,4-butylene 2,5-furandicarboxylate), poly(1,4-butylene azelaic acid-co-1,4-butylene 2,5-furandicarboxylate). 1,4-butylene glycol-co-1,4-butylene sebacate-co-1,4-butylene 2,5-furandicarboxylate), poly(1,4-butylene adipate-co-1,4-butylene azelaic acid-co-1,4-butylene 2,5-furandicarboxylate), poly(1,4-butylene succinate-co-1,4-butylene sebacate-co-1,4-butylene 2,5-furandicarboxylate), poly(1,4-butylene adipate-co-1,4-butylene succinate-co-1,4-butylene 2,5-furandicarboxylate), poly(1,4-butylene azelaic acid-co-1,4-butylene succinate-co-1,4-butylene 2,5-furandicarboxylate).

[0099] In another preferred embodiment of the present invention, the diacid-diol polyester that is not polyester i. is selected from the group consisting of: poly(1,4-butylene succinate), poly(1,4-butylene sebacate), poly(1,2-ethylene sebacate), poly(1,4-butylene adipate-co-1,4-butylene sebacate-co-1,4-butylene terephthalate), poly(1,4-butylene adipate-co-1,4-butylene sebacate-co-1,4-butylene terephthalate), poly(1,4-butylene adipate-co-1,4-butylene terephthalate), poly(1,4-butylene adipate-co-1,4-butylene terephthalate), poly(1,4-butylene adipate-co-1,4-butylene terephthalate). 4-butylene glycol ester-co-1,4-butylene glycol azelaate-co-1,4-butylene glycol terephthalate), poly(1,4-butylene glycol sebacate-co-1,4-butylene glycol terephthalate), poly(1,4-butylene glycol azelaate-co-1,4-butylene glycol terephthalate), poly(1,4-butylene glycol adipate-co-1,4-butylene glycol terephthalate).

[0100] In an even more preferred embodiment of the present invention, the diacid diol polyester which is not polyester i. is selected from the group consisting of: poly(1,4-butylene succinate), poly(1,4-butylene adipate-co-1,4-butylene terephthalate).

[0101] The polymer ii. of the composition according to the invention is biodegradable. In the sense of the present invention, a so-called biodegradable polymer is a biodegradable polymer according to standard EN 13432.

[0102] In the composition according to the invention, fillers (component iii.) help to improve dimensional stability and are preferably selected from kaolin, barite, clay, talc, calcium and magnesium carbonate, iron and lead, aluminum hydroxide, diatomaceous earth, aluminum sulfate, barium sulfate, silicon dioxide, mica, titanium dioxide, wollastonite, starch, chitin, chitosan, alginates, proteins such as gluten, zein, casein, collagen, gelatin, natural gums, rosin acid and their derivatives.

[0103] The term "starch" refers here to all types of starch, i.e. flour, natural starch, hydrolyzed starch, destructured starch, gelatinized starch, plasticized starch, thermoplastic starch, biological fillers containing complex starch or mixtures thereof. Particularly suitable according to the invention are starches such as potato, corn, cassava and pea starch.

[0104] Starches which can be easily denatured and have a high initial molecular weight, such as potato or corn starch, have proven to be particularly advantageous.

[0105] The starch may be present as such or in chemically modified form, for example in the form of starch esters having a degree of substitution of 0.2 to 2.5, hydroxypropylated starch or fatty chain-modified starch.

[0106] Reference is made here to "modified starch" with reference to the teaching contained in patents EP-0 118 240 and EP-0 327 505, which refers to starch that has been processed so that it has essentially no so-called "Maltes crosses" in polarized light under an optical microscope and essentially no so-called "ghost images" under a phase contrast optical microscope.

[0107] Advantageously, the starch is modified by means of an extrusion process at a temperature of 110-250° C., preferably 130-180° C., preferably at a pressure of 0.1-7 MPa, preferably 0.3-6 MPa, thereby preferably providing a specific energy of more than 0.1 kWh / kg during said extrusion.

[0108] The starch is preferably denatured in the presence of 1-40% by weight, relative to the weight of the starch, of one or more plasticizers selected from water and polyols containing 2-22 carbon atoms. As for water, it can also be water naturally present in the starch. Among the polyols, preferred ones are polyols having 1-20 hydroxyl groups and containing 2-6 carbon atoms, their ethers, thioethers, and organic and inorganic esters. Examples of polyols are glycerol, diglycerol, polyglycerol, pentaerythritol, polyglycerol ethoxylates, ethylene glycol, polyethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, neopentyl glycol, sorbitol monoacetate, sorbitol diacetate, sorbitol monoethoxylate, sorbitol diethoxylate and mixtures thereof. In a preferred embodiment, the starch is denatured in the presence of glycerol or a mixture of plasticizers containing glycerol, more preferably containing 2-90% by weight of glycerol. Preferably, the modified and cross-linked starch according to the invention comprises 1-40% by weight of plasticizer, relative to the weight of the starch.

[0109] When present, the starch in the composition is preferably present in the form of particles having a circular or elliptical cross-section or in any case a cross-section that can resemble an ellipse with an arithmetic mean diameter of less than 1 micron, preferably less than 0.5 μm, measured taking into account the major axes of the particles.

[0110] In a preferred embodiment of the invention, the filler comprises talc, calcium carbonate or a mixture thereof in the form of particles having an arithmetic mean diameter, measured taking into account the major axis of the particles, of less than 10 micrometers. It has in fact been found that fillers of the above-mentioned type, which are not characterized by said arithmetic mean diameter, do not improve the disintegrability properties of the molded bodies containing them less significantly during industrial composting. Without wishing to be bound by any particular theory, it is felt that when used in the composition according to the invention, said filler becomes stratified and agglomerated during the molding stage, thereby slowing down the action of the agent that disintegrates the molded article.

[0111] In the composition according to the invention, the vegetable fibers (component iv.) are preferably selected from cellulose fibers, wood flour, hemp fibers, lignocellulosic residues of raw materials originating from vegetable sources, such as thistle or sunflower plants and grass cuttings.

[0112] The polymer composition according to the invention preferably comprises up to 30% by weight of vegetable fibers (component iv.). It has in fact been found that this content has the effect of significantly improving the crushability properties of the polymer composition, while making it possible to produce articles having a high heat deflection temperature and a particularly high dimensional stability under load, thereby making it possible to prepare compositions that are also free of fillers.

[0113] In a preferred embodiment, the composition according to the invention comprises 5 to 25% by weight of vegetable fibers. In particular, such a vegetable fiber content is particularly suitable for use in the composition according to the invention in injection molding technology.

[0114] The so-called "dimensional stability" refers to the ability of an object to maintain its original shape over time or after annealing.

[0115] It has also been surprisingly found that the use of plant fibers having a length / diameter ratio (i.e. L / D) <40, preferably L / D <30, even more preferably L / D <20 has proven to be particularly advantageous since, in addition to contributing to the above-mentioned properties of dimensional stability and high heat deflection temperature, it neither leads to an excessive increase in the tensile modulus or a significant reduction in the deformation of the polymer composition when failing, nor to a significant reduction in its flowability in the molten state.

[0116] Particularly preferred examples of compositions according to the invention are:

[0117] - Composition A, comprising, relative to the total amount of components i. to iv.:

[0118] i) 20-60% by weight, preferably 25-55% by weight, more preferably 25-50% by weight of at least one biodegradable polyester i.;

[0119] ii) 20 to 70% by weight, preferably 25 to 65% by weight, of at least one polyhydroxyalkanoate;

[0120] iii) 0-50 wt %, preferably 3-45 wt %, more preferably 5-40 wt % of at least one filler;

[0121] iv) 0-30 wt.% vegetable fibers.

[0122] - Composition B, comprising, relative to the total amount of components i. to iv.:

[0123] i) 20-60% by weight, preferably 25-55% by weight, more preferably 25-50% by weight of at least one biodegradable polyester i.;

[0124] ii) 20 to 70% by weight, preferably 25 to 65% by weight, of at least one aliphatic diacid diol polyester;

[0125] iii) 0-50 wt %, preferably 3-45 wt %, more preferably 5-40 wt % of at least one filler;

[0126] iv) 0-30 wt.% vegetable fibers.

[0127] - Composition C, comprising, relative to the total amount of components i. to iv.:

[0128] i) 20-60% by weight, preferably 25-55% by weight, more preferably 25-50% by weight of at least one biodegradable polyester i.;

[0129] ii) 20 to 70% by weight, preferably 25 to 65% by weight, of at least one aliphatic-aromatic diacid diol polyester;

[0130] iii) 0-50 wt %, preferably 3-45 wt %, more preferably 5-40 wt % of at least one filler;

[0131] iv) 0-30 wt.% vegetable fibers.

[0132] - Composition D comprising, relative to the total amount of components i.-iii:

[0133] i) 20-60% by weight, preferably 25-55% by weight, more preferably 25-50% by weight of at least one biodegradable polyester i.;

[0134] ii) 20 to 70% by weight, preferably 25 to 65% by weight, of at least one polyhydroxyalkanoate;

[0135] iii) 3 to 45 wt. %, more preferably 5 to 40 wt. % of at least one filler.

[0136] - Composition E, comprising, relative to the total amount of components i. to iii.:

[0137] i) 20-60% by weight, preferably 25-55% by weight, more preferably 25-50% by weight of at least one biodegradable polyester i.;

[0138] ii) 20 to 70% by weight, preferably 25 to 65% by weight, of at least one aliphatic diacid diol polyester;

[0139] iii) 3 to 45 wt. %, more preferably 5 to 40 wt. % of at least one filler.

[0140] - Composition F comprising, relative to the total amount of components i. to iii.:

[0141] i) 20-60% by weight, preferably 25-55% by weight, more preferably 25-50% by weight of at least one biodegradable polyester i.;

[0142] ii) 20 to 70% by weight, preferably 25 to 65% by weight, of at least one aliphatic-aromatic diacid diol polyester;

[0143] iii) 3 to 45 wt. %, more preferably 5 to 40 wt. % of at least one filler.

[0144] - Composition G, comprising, relative to the total amount of components i. to iv.:

[0145] i) 25-50% by weight of at least one biodegradable polyester i.;

[0146] ii) 25-65% by weight of at least one polyhydroxyalkanoate;

[0147] iii) 0-50 wt %, preferably 3-45 wt %, more preferably 5-40 wt % of at least one filler;

[0148] iv) 0-30 wt.% vegetable fibers.

[0149] - Composition H comprising, relative to the total amount of components i. to iv.:

[0150] i) 25-50% by weight of at least one biodegradable polyester i.;

[0151] ii) 25 to 65 wt. % of at least one aliphatic diacid diol polyester;

[0152] iii) 0-50 wt %, preferably 3-45 wt %, more preferably 5-40 wt % of at least one filler;

[0153] iv) 0-30 wt.% vegetable fibers.

[0154] - Composition I, comprising, relative to the total amount of components i. to iv.:

[0155] i) 25-50% by weight of at least one biodegradable polyester i.;

[0156] ii) 25 to 65% by weight of at least one aliphatic-aromatic diacid diol polyester;

[0157] iii) 0-50 wt %, preferably 3-45 wt %, more preferably 5-40 wt % of at least one filler;

[0158] iv) 0-30 wt.% vegetable fibers.

[0159] In addition to components i. to iv., the composition according to the invention may also contain up to 5% by weight of a crosslinker and / or a chain extender, relative to the total weight of the composition. The crosslinker and / or chain extender improves the hydrolytic stability and is chosen from compounds having two and / or more functional groups, including isocyanates, peroxides, carbodiimides, isocyanurates, Preferably, the crosslinking agent and / or chain extender comprises at least one compound having two and / or more functional groups, the functional groups comprising isocyanate groups. More preferably, the crosslinking agent and / or chain extender comprises at least 25% by weight of one or more compounds having two and / or more functional groups, the functional groups comprising isocyanate groups. Particularly preferred are mixtures of compounds having two and / or more functional groups comprising isocyanate groups and compounds having two and / or more functional groups comprising epoxide groups, and even more preferably comprising at least 75% by weight of compounds having two and / or more functional groups comprising isocyanate groups.

[0160] The compound having two or more functional groups including an isocyanate group is preferably selected from p-phenylene diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4-diphenylmethane-diisocyanate, 1,3-phenylene-4-chlorodiisocyanate, 1,5-naphthalene diisocyanate, 4,4-diphenylene diisocyanate, 3,3'-dimethyl-4,4-diphenylmethane diisocyanate, 3-methyl-4,4'-diphenylmethane diisocyanate, diphenyl ester diisocyanate, 2,4-cyclohexane diisocyanate, 2,3-cyclohexane diisocyanate, 1- Methyl 2,4-cyclohexyl diisocyanate, 1-methyl 2,6-cyclohexyl diisocyanate, bis-(isocyanate cyclohexyl) methane, 2,4,6-toluene triisocyanate, 2,4,4-diphenyl ether triisocyanate, polymethylene-polyphenyl-polyisocyanate, methylene diphenyl diisocyanate, triphenylmethane triisocyanate, 3,3'-dimethylbenzene-4,4-diisocyanate, 4,4'-methylenebis(2-methyl-phenylisocyanate), hexamethylene diisocyanate, 1,3-cyclohexylene diisocyanate, 1,2-cyclohexylene diisocyanate and mixtures thereof. In a preferred embodiment, the compound comprising an isocyanate group is 4,4-diphenylmethane diisocyanate.

[0161] As for the compounds having two or more functional groups containing peroxide groups, they are preferably selected from benzoyl peroxide, lauroyl peroxide, isononanoyl peroxide, di-(tert-butylperoxyisopropyl)benzene, tert-butyl peroxide, dicumyl peroxide, α,α′-di(tert-butylperoxy)diisopropylbenzene, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, tert-butylisopropylbenzene peroxide, di-tert-butyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hex-3-yne, di(4-tert-butylcyclohexyl)peroxydicarbonate, dicetyl peroxydicarbonate, dimyristyl peroxydicarbonate, 3,6,9-triethyl-3,6,9-trimethyl-1,4,7-triperoxonane, di(2-ethylhexyl)peroxydicarbonate and mixtures thereof.

[0162] Compounds having two or more functional groups including carbodiimide groups which are preferably used in the composition according to the invention are selected from poly(cyclooctenecarbodiimide), poly(1,4-dimethylenecyclohexenecarbodiimide), poly(cyclohexenecarbodiimide), poly(ethylenecarbodiimide), poly(butylenecarbodiimide), poly(isobutylenecarbodiimide), poly(nonenecarbodiimide), poly(dodecenecarbodiimide), poly(neopentenecarbodiimide), poly(1,4-dimethylenephenylenecarbodiimide), poly(2,2′,6,6′-tetraisopropyldiphenylenecarbodiimide) D), poly (2,4,6-triisopropyl-1,3-phenylenecarbodiimide) ( P-100), poly (2,6-diisopropyl-1,3-phenylenecarbodiimide) ( P), poly(tolylcarbodiimide), poly(4,4'-diphenylmethanecarbodiimide), poly(3,3'-dimethyl-4,4'-biphenylenecarbodiimide), poly(p-phenylenecarbodiimide), poly(m-phenylenecarbodiimide), poly(3,3'-dimethyl-4,4'-diphenylmethanecarbodiimide), poly(naphthalenecarbodiimide), poly(isophoronecarbodiimide), poly(cumenecarbodiimide), p-phenylenebis(ethylcarbodiimide), 1,6-hexamethylenebis(ethylcarbodiimide), 1,8-octamethylenebis(ethylcarbodiimide), 1,10-decamethylenebis(ethylcarbodiimide), 1,12-dodecamethylenebis(ethylcarbodiimide), and mixtures thereof.

[0163] Examples of compounds having two or more functional groups including epoxide groups which can be advantageously used in the composition according to the invention are all polyepoxides obtained from epoxylated oils and / or styrene-glycidyl ether-methyl methacrylate, glycidyl ether methyl methacrylate, including all polyepoxides having a molecular weight of 1000 to 10000 and having an epoxide number per molecule of 1 to 30, preferably 5 to 25, and epoxides selected from the group comprising diethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, glycerol polyglycidyl ether, diglycerol polyglycidyl ether, 1,2-butylene oxide, polyglycerol polyglycidyl ether, isoprene diepoxide and alicyclic diepoxides, 1,4-cyclohexanedimethanol diglycidyl ether, glycidyl 2-methylphenyl ether, glycerol propoxylatriglycidyl ether. ether), 1,4-butanediol diglycidyl ether, sorbitol polyglycidyl ether, glycerol diglycidyl ether, meta-xylene diamine tetraglycidyl ether and bisphenol A diglycidyl ether and mixtures thereof.

[0164] The catalyst can also be used with two or more compounds including isocyanates, peroxides, carbodiimides, isocyanurates, Compounds functionalized with oxazolines, epoxides, anhydrides and divinyl ether groups are used together in the composition according to the invention to increase the reactivity of the reactive groups. In the case of polyepoxides, preferably fatty acid salts are used, even more preferably calcium and zinc stearates.

[0165] In a particularly preferred embodiment of the present invention, the crosslinker and / or chain extender in the composition comprises a compound comprising an isocyanate group, preferably 4,4-diphenylmethane diisocyanate, and / or a compound comprising a carbodiimide group, and / or a compound comprising an epoxide group, preferably a styrene-glycidyl ether-methyl methacrylate type compound.

[0166] Besides components i. to iv., the composition according to the invention may also comprise up to 15% by weight, preferably up to 10% by weight, more preferably up to 5% by weight, of non-biodegradable polymers, relative to the total weight of the composition.

[0167] The non-biodegradable polymer is advantageously chosen from vinyl polymers, diacid diol polyesters which are not polyesters i. or ii., polyamides, polyurethanes, polyethers, polyureas, polycarbonates and mixtures thereof.

[0168] Among the vinyl polymers, preferred ones are: polyethylene, polypropylene, their copolymers, polyvinyl alcohol, polyvinyl acetate, polyethylvinyl acetate and polyethylene vinyl alcohol, polystyrene, chlorinated vinyl polymers, polyacrylates.

[0169] Among the chlorinated ethylene-based polymers, those understood to be included herein are, in addition to polyvinyl chloride, polyvinylidene chloride, polyvinyl chloride, poly(vinyl chloride-vinyl acetate), poly(vinyl chloride-ethylene), poly(vinyl chloride-propylene), poly(vinyl chloride-styrene), poly(vinyl chloride-isobutylene) and copolymers in which polyvinyl chloride accounts for more than 50 mole %. The copolymers may be random, block or alternating copolymers.

[0170] As regards the diacid diol polyesters which are not polyesters i. or ii., they are preferably selected from polyesters comprising:

[0171] a) a dicarboxylic acid component, comprising, relative to the total dicarboxylic acid component:

[0172] a11) 50-100 mol %, preferably 60-100 mol % of one or more aromatic diacids, their esters or salts;

[0173] a12) 0-50 mol %, preferably 0-40 mol % of one or more aliphatic diacids, their esters or salts;

[0174] b) a diol component comprising derivative units relative to the total diol component:

[0175] b1) 95 to 100 mol % of units derived from at least one saturated aliphatic diol;

[0176] b2) 0 to 5 mol % of units derived from at least one unsaturated aliphatic diol.

[0177] Preferably, the aromatic dicarboxylic acids, saturated aliphatic dicarboxylic acids, unsaturated aliphatic dicarboxylic acids, saturated aliphatic diols and unsaturated aliphatic diols of the polyester are selected from those described above for the polyesters according to the invention (components i. and ii.). More preferably, the diacid diol polyesters other than polyesters i. and ii. are selected from block or random copolymers of the poly(ethylene terephthalate), poly(propylene terephthalate), poly(butylene terephthalate), poly(ethylene 2,5-furandicarboxylate), poly(propylene 2,5-furandicarboxylate), poly(butylene 2,5-furandicarboxylate) and poly(alkylene 2,5-furandicarboxylate-co-alkylene terephthalate), poly(alkylene terephthalate-co-alkylene alkanoate) or poly(alkylene 2,5-furandicarboxylate-co-alkylene alkanoate) type. Preferred examples of diacid diol polyesters other than polyesters i. and ii. are selected from the group consisting of poly(1,4-butylene adipate-co-1,4-butylene terephthalate), poly(1,4-butylene sebacate-co-1,4-butylene terephthalate), poly(1,4-butylene azelate-co-1,4-butylene terephthalate), poly(1,4-butylene brassylate-co-1,4-butylene terephthalate), poly(1,4-butylene succinate-co-1,4-butylene terephthalate). 1,4-butylene glycol ester), poly(1,4-butylene adipate-co-1,4-butylene sebacate-co-1,4-butylene terephthalate), poly(1,4-butylene azelaic acid-co-1,4-butylene sebacate-co-1,4-butylene terephthalate), poly(1,4-butylene adipate-co-1,4-butylene azelaic acid-co-1,4-butylene terephthalate), poly(1,4-butylene succinate-co-1,4-butylene sebacate) 1,4-butylene glycol ester-co-1,4-butylene terephthalate), poly(1,4-butylene adipate-co-1,4-butylene succinate-co-1,4-butylene terephthalate), poly(1,4-butylene azelaic acid-co-1,4-butylene succinate-co-1,4-butylene terephthalate), poly(1,4-butylene adipate-co-1,4-butylene 2,5-furan dicarboxylic acid), poly(1,4-butylene sebacate-co-2,5-furan dicarboxylic acid 1,4-butylene glycol ester), poly(1,4-butylene glycol azelaic acid-co-1,4-butylene glycol 2,5-furan dicarboxylate), poly(1,4-butylene glycol brazyl acid-co-1,4-butylene glycol 2,5-furan dicarboxylate), poly(1,4-butylene glycol succinate-co-1,4-butylene glycol 2,5-furan dicarboxylate), poly(1,4-butylene glycol adipate-co-1,4-butylene glycol sebacate-co-1,4-butylene glycol 2,5-furan dicarboxylate), poly(1,4-butylene glycol azelaic acid-co-1,4-butylene glycol sebacate-co-1,4-butylene glycol 2,5-furan dicarboxylate), poly(1,4-butylene glycol azelaic acid-co-1,4-butylene glycol succinate-co-1,4-butylene glycol 2,5-furan dicarboxylate),4-butylene glycol ester-co-1,4-butylene glycol sebacate-co-1,4-butylene glycol 2,5-furan dicarboxylate), poly(1,4-butylene glycol adipate-co-1,4-butylene glycol azelaic acid-co-1,4-butylene glycol 2,5-furan dicarboxylate), poly(1,4-butylene glycol succinate-co-1,4-butylene glycol sebacate-co-1,4-butylene glycol 2,5-furan dicarboxylate), poly(1,4-butylene glycol adipate-co-1,4-butylene glycol succinate-co-2,5-furan dicarboxylate). 1,4-butylene glycol ester), poly(1,4-butylene glycol azelaic acid-co-1,4-butylene glycol succinate-co-1,4-butylene glycol 2,5-furandicarboxylate), poly(1,2-ethylene glycol adipate-co-1,2-2,5-furandicarboxylate), poly(1,2-ethylene glycol sebacate-co-1,2-2,5-furandicarboxylate), poly(1,2-ethylene glycol azelaic acid-co-1,2-2,5-furandicarboxylate), poly(1,2-ethylene glycol brazilate-co- -1,2-2,5-furandicarboxylic acid ethylene glycol ester), poly(1,2-ethylene glycol succinate-co-1,2-2,5-furandicarboxylic acid ethylene glycol ester), poly(1,2-ethylene glycol adipate-co-1,2-ethylene glycol sebacate-co-1,2-2,5-furandicarboxylic acid ethylene glycol ester), poly(1,2-ethylene glycol azelaic acid-co-1,2-ethylene glycol sebacate-co-1,2-2,5-furandicarboxylic acid ethylene glycol ester), poly(1,2-ethylene glycol adipate-co-1,2-ethylene glycol azelaic acid ethylene glycol ester -co-1,2-2,5-furandicarboxylic acid ethylene glycol ester), poly(1,2-ethylene glycol succinate-co-1,2-ethylene glycol sebacate-co-1,2-2,5-furandicarboxylic acid ethylene glycol ester), poly(1,2-ethylene glycol adipate-co-1,2-ethylene glycol succinate-co-1,2-2,5-furandicarboxylic acid ethylene glycol ester), poly(1,2-ethylene glycol azelaic acid-co-1,2-ethylene glycol succinate-co-1,2-2,5-furandicarboxylic acid ethylene glycol ester), their copolymers and mixtures.

[0178] As for the polyamides in the composition according to the invention, they are preferably chosen from polyamides 6 and 6,6, polyamides 9 and 9,9, polyamides 10 and 10,10, polyamides 11 and 11,11, polyamides 12 and 12,12 and combinations thereof of the 6 / 9, 6 / 10, 6 / 11, 6 / 12 type, their mixtures and random and block copolymers.

[0179] Preferably, the polycarbonate in the composition according to the invention is chosen from polyalkylene carbonates, more preferably polyethylene carbonate, polypropylene carbonate, polybutylene carbonate, mixtures thereof and random and block copolymers.

[0180] Among the polyethers, preferred ones are those selected from polyethylene glycol, polypropylene glycol, polybutylene glycol, copolymers thereof and mixtures thereof having a molecular weight of 70,000-500,000.

[0181] In addition to components i. to iv., the composition according to the invention preferably also contains at least one further component selected from the group consisting of plasticizers, UV stabilizers, lubricants, nucleating agents, surfactants, antistatic agents, pigments, flame retardants, compatibilizers, lignin, organic acids, antioxidants, mildewcides, waxes and processing aids.

[0182] As for plasticizers, in addition to any plasticizers preferably used for preparing the modified starch described above, preferably one or more plasticizers selected from phthalates, such as diisononyl phthalate, trimellitic acid esters, such as trimellitic acid and C4-C 20 Esters of monohydric alcohols (which are preferably selected from n-octanol and n-decanol), and plasticizers in aliphatic esters having the following structure:

[0183] R1-OC(O)-R4-C(O)-[-O-R2-OC(O)-R5-C(O)-] m -O-R3

[0184] in:

[0185] R1 is selected from one or more of the following groups: H, C1-C 24 Types of saturated and unsaturated linear and branched alkyl residues, with C1-C 24 A polyol residue esterified with a monocarboxylic acid;

[0186] R2 comprises a -CH2-C(CH3)2-CH2- group and a C2-C8 alkylene group, and comprises at least 50 mol% of the -CH2-C(CH3)2-CH2- group;

[0187] R3 is selected from one or more of the following groups: H, C1-C 24 Types of saturated and unsaturated linear and branched alkyl residues, with C1-C 24 A polyol residue esterified with a monocarboxylic acid;

[0188] R4 and R5 are the same or different and contain one or more C2-C 22 , preferably C2-C 11 , more preferably C4-C9 alkylene and including at least 50 mol% of C7 alkylene.

[0189] m is a value of 1 to 20, preferably 2 to 10, more preferably 3 to 7. Preferably, in the ester, at least one of R1 and / or R3 comprises at least one C1-C24 A polyol residue esterified with a monocarboxylic acid selected from stearic acid, palmitic acid, 9-keto stearic acid, 10-keto stearic acid and mixtures thereof, preferably in an amount of ≥10 mol %, more preferably ≥20 mol %, even more preferably ≥25 mol % relative to the total amount of R1 and / or R3 groups. Examples of aliphatic esters of this type are described in Italian patent application MI2014A000030 and PCT applications PCT / EP2015 / 050336, PCT / EP2015 / 050338.

[0190] When present, the selected plasticizer is preferably present at up to 10% by weight relative to the total weight of the composition.

[0191] The lubricant is preferably chosen from esters and metal salts of fatty acids such as zinc stearate, calcium stearate, aluminum stearate and acetyl stearate.Preferably, the composition according to the invention comprises at most 1% by weight of lubricant, more preferably at most 0.5% by weight, relative to the total weight of the composition.

[0192] Examples of nucleating agents include sodium salt of saccharin, calcium silicate, sodium benzoate, calcium titanate, boron nitride, isotactic polypropylene and low molecular weight PLA. These additives are preferably added in an amount of up to 10% by weight, more preferably 2-6% by weight, relative to the total weight of the composition.

[0193] If necessary, pigments such as titanium dioxide, clay, copper phthalocyanine, iron silicates, oxides and hydroxides, carbon black and magnesium oxide may also be added. These additives preferably total 10% by weight.

[0194] The preparation method of the polymer composition according to the present invention can be carried out according to any method known in the prior art. Advantageously, the composition according to the present invention is obtained via an extrusion process, wherein the polymer components are mixed in a molten state. When the composition is extruded, all components can be supplied together or one or more of them can be supplied separately along the extruder.

[0195] The compositions according to the invention are extremely suitable for use in many practical applications for the manufacture of products such as films, fibers, nonwoven fabrics, sheets, molded, thermoformed, blown or expanded articles and laminated articles including using extrusion coating techniques.

[0196] The composition according to the invention is biodegradable. In the meaning of the present invention, a composition is meant to be biodegradable when it exhibits a decomposition higher than 90% in 90 days according to standard ISO 20200:2004.

[0197] Preferably, the composition according to the invention is biodegradable according to standard EN 13432.

[0198] The composition according to the invention is characterized by a G' modulus value obtained at 70°C via Dynamic Mechanical-Torsion Analysis (DMTA) higher than 40 MPa, preferably higher than 50 MPa.

[0199] The compositions according to the invention are distinguished by high barrier properties towards oxygen, carbon dioxide and water vapour.

[0200] The composition according to the invention has:

[0201] Less than 20 (cm2) measured according to standard ASTM F2622-08 at 23°C-50% relative humidity 3 ×mm) / (m 2 × 24h × bar) against oxygen permeation barrier, and

[0202] Less than 45 (cm2) measured according to standard ASTM F2476-05 at 23°C-50% relative humidity 3 ×mm) / (m 2 × 24h × bar) against the permeation barrier of carbon dioxide, and

[0203] Less than 80 (g×30 μm) / (m 2 × 24h) permeation barrier against water vapor transmission (WVTR).

[0204] The melt volume-flow rate (MVR) of the composition according to the invention is measured according to standard ISO 1133-1 at 190° C., 2.16 kg and is 1-40 cm 3 / 10min, preferably 2-30cm 3 / 10min.

[0205] Preferably, the composition according to the invention is characterized by excellent mechanical properties, especially high tensile strength, elongation and tensile modulus.

[0206] The invention also relates to a preparation comprising the composition according to the invention.

[0207] Examples of products comprising the composition according to the invention are:

[0208] - films (both mono- and bi-oriented), and multilayer films formed with other polymeric materials;

[0209] - Films for use as covering films in the agricultural sector;

[0210] - stretch films (including cling films) for food, for baling in agriculture and for wrapping waste;

[0211] -Bags and liners for organic matter collection such as food waste and grass cuttings;

[0212] - Thermoformed food packaging (monolayer and multilayer), e.g. containers for milk, yoghurt, meat, beverages, etc.;

[0213] - coatings obtained using extrusion coating technology;

[0214] - multilayer laminates containing layers of paper, plastic, aluminium, metallized films;

[0215] - expanded or expandable beads for the preparation of components formed by sintering;

[0216] - expanded and semi-expanded products including expanded masses formed from pre-expanded granules;

[0217] - Expanded sheets, thermoformed expanded sheets, containers obtained therefrom for food packaging;

[0218] -Containers generally used for fruits and vegetables;

[0219] - Composite materials containing gelatinized, modified and / or complexed starch, native starch, flour, other fillers of natural plant or inorganic origin as fillers;

[0220] - Fibers, microfibers, composite fibers with a core containing a rigid polymer such as PLA, PET, PTT, etc. and an external sheath of the material of the invention, deblens composite fibers, fibers with various cross-sections from round to multilobal, flocculate fibers, fabrics and nonwoven, spunbonded or thermally bonded fabrics for use in the hygiene, health, agriculture and clothing sectors.

[0221] It can also be used as a replacement for plasticized PVC in applications.

[0222] The compositions according to the invention are also particularly suitable for injection moulding and thermoforming, and for spinning.

[0223] The properties of the composition according to the invention in fact make it possible to manufacture injection-molded or thermoformed articles having a high heat deflection temperature (HDT) and high dimensional stability. For example, the composition according to the invention is particularly suitable for preparing disposable cutlery, plates and cups, rigid containers, capsules for delivering beverages, preferably hot beverages, caps and lids, and food packaging that can be heated in conventional and microwave ovens.

[0224] In a preferred embodiment of the present invention, the thermoformed article comprises at least one layer A and at least one layer B, the at least one layer A comprising or consisting of a composition comprising or consisting of a polyester according to the present invention, the at least one layer B comprising at least one polymer selected from the group comprising diacid diol polyesters and hydroxy acid polyesters, and preferably characterized by a mutual arrangement of the layers A and B selected from A / B, A / B / A and B / A / B. In another particularly preferred embodiment, the layer B comprises a lactic acid polyester.

[0225] As for the molding process by thermoforming, the composition according to the invention can be molded under pressure or under vacuum, for example starting from a sheet, slab or film, according to methods known to those skilled in the art. The invention also relates to said sheet, slab or film for the preparation of articles molded by thermoforming, comprising the composition according to the invention.

[0226] Typical thermoforming operating conditions provide a heating time of, for example, 5 to 8 seconds for the sheet, mat or film until softened, and a molding time of 15 to 20 seconds.

[0227] As for injection molding, the compositions according to the invention have another advantage, namely that they can be fed to common machines without requiring significant changes to normal working conditions, compared with other conventional polymers such as polyethylene, polypropylene, polystyrene and ABS. Preferably, in the case of objects with a maximum thickness of about 1 mm, they can be molded using melt temperatures of 180-240° C., oleodynamic pressures of 7-110 bar, cooling times of 3-15 seconds and cycle times of 10-30 seconds.

[0228] In a particularly preferred embodiment, the injection-molded article comprising the composition according to the invention is subjected to a thermal annealing treatment at a temperature of 70-150° C. The invention also relates to the article obtained by means of the annealing treatment (referred to as annealed product).

[0229] The annealing treatment can advantageously be carried out at a constant temperature in an unconstrained environment, for example in a furnace. In this case, the annealing treatment is preferably carried out at a temperature of 80-150° C. for 30 seconds to 60 minutes, preferably 40 seconds to 30 minutes, even more preferably 40 seconds to 5 minutes, and is therefore particularly advantageous from a production perspective. The specific conditions that must be used will vary depending on the size of the object that must undergo the annealing treatment and the degree of heat resistance required by the application. In general, in the case of thick objects, it is preferred to use higher temperatures or longer residence times.

[0230] The annealing treatment may also be carried out in a constrained environment, for example in a preheated mould at a constant temperature, preferably at 80-100°C for 1-5 minutes. The specific conditions that must be used will vary depending on the size of the object undergoing the annealing treatment. In general, in the case of thick objects, it is preferred to use longer residence times.

[0231] The invention will now be described by means of a number of embodiments which are to be considered as examples and not as limiting the scope of protection of the present patent application. Example

[0232] In the case of 0.07m 3 The synthesis of components i, ii-1, ii-3 and ii-4 was carried out in a stainless steel intermittent one-pot polymerization apparatus of geometric volume. The reactor was equipped with a nitrogen inlet, a circulating oil heating system, a stirring device equipped with an electric motor, a distillation line with a column (structured packing), a condenser and a collecting container, and a vacuum line with a condenser, a cooling trap and a vacuum rotary pump.

[0233] Component i: poly(1,2-ethylene glycol azelaate-co-1,2-ethylene glycol 2,5-furandicarboxylate)

[0234] 12.3 kg 2,5-furandicarboxylic acid, 4.95 kg azelaic acid, 9.79 kg ethylene glycol, 58.1 g glycerol and 8 g TE was fed into the reactor under a nitrogen blanket, and then 3 vacuum / nitrogen cycles were applied in order to remove water and oxygen traces from the vessel. The temperature was gradually raised to 220° C. and the reaction was carried out in a nitrogen stream until a conversion of 140% was reached (calculated as the ratio of the amount of distillate to the theoretical value of stoichiometric water). Thereafter, a vacuum ramp to 200 mbar was implemented in about 30 minutes in order to remove the large excess of ethylene glycol. Nitrogen was pumped into the reactor to set the pressure to ambient pressure, and after adding After TnBT, the pressure was gradually reduced from atmospheric pressure to high vacuum (p<2 mbar) within 45 minutes and the temperature was set to 238°C. Polymerization was carried out until the desired molecular weight was reached. The molecular weight was estimated using the torque measured at the stirring shaft. At the end of the polymerization stage, nitrogen was pumped into the container to offset the vacuum. The polymer was then discharged in the form of strands, cooled in a cold water bath, granulated using a granulator and dried.

[0235] Component ii-1: Poly(1,4-butylene succinate)

[0236] 13.7 kg succinic acid, 12.0 kg 1,4-butanediol, 42.7 g glycerol and 2 g TE was fed into the reactor under a nitrogen blanket and the temperature was gradually raised to 230°C. The reaction was carried out in a nitrogen stream until a conversion of 130% (calculated as the ratio of the amount of distillate to the theoretical value of stoichiometric water) was reached. After TnBT, the pressure was gradually reduced from atmospheric pressure to high vacuum (p<2 mbar) within 45 minutes and the temperature was set to 235°C. Polymerization was carried out until the desired molecular weight was reached. The molecular weight was estimated using the torque measured at the stirring shaft. At the end of the polymerization stage, nitrogen was pumped into the container to offset the vacuum. The polymer was then discharged in the form of strands, cooled in a cold water bath, granulated using a granulator and dried.

[0237] Component ii-2: Polylactic acid Ingeo 3251D, MFR 35 / 10min (@190℃, 2.16kg).

[0238] Component ii-3: poly(1,4-butylene adipate-co-1,4-butylene azelate-co-1,4-butylene terephthalate)

[0239] 7.22Kg terephthalic acid, 5.01Kg adipic acid, 2.77Kg azelaic acid, 10.83Kg 1,4-butanediol, 4.26g glycerol and 2g TE was fed into the reactor under a nitrogen blanket and the temperature was gradually raised to 220°C. The reaction was carried out in a nitrogen stream until a conversion of 120% (calculated as the ratio of the amount of distillate to the theoretical value of stoichiometric water) was reached. After TnBT, the pressure was gradually reduced from atmospheric pressure to high vacuum (p<2 mbar) within 45 minutes and the temperature was set to 235°C. Polymerization was carried out until the desired molecular weight was reached. The molecular weight was estimated using the torque measured at the stirring shaft. At the end of the polymerization stage, nitrogen was pumped into the container to offset the vacuum. The polymer was then discharged in the form of strands, cooled in a cold water bath, granulated using a granulator and dried.

[0240] Component ii-4: Poly(ethylene sebacate)

[0241] 17.7Kg of sebacic acid, 6.25Kg of ethylene glycol, 40.4g of glycerol and 2g TE was fed into the reactor under a nitrogen blanket and the temperature was gradually raised to 220°C. The reaction was carried out in a nitrogen stream until a conversion of 105% (calculated as the ratio of the amount of distillate to the theoretical value of stoichiometric water) was reached. After TnBT, the pressure was gradually reduced from atmospheric pressure to high vacuum (p<2 mbar) within 45 minutes and the temperature was set to 235°C. Polymerization was carried out until the desired molecular weight was reached. The molecular weight was estimated using the torque measured at the stirring shaft. At the end of the polymerization stage, nitrogen was pumped into the container to offset the vacuum. The polymer was then discharged in the form of strands, cooled in a cold water bath, granulated using a granulator and dried.

[0242] Component iii: micronized talc with a median diameter of 1 micron (particle size distribution by Sedigraph according to ISO 13317-3), Jetfine 3CA, technical grade from Imerys.

[0243] Component iv: Fibrillar cellulose fibers with an average fiber length of 550 microns, L / D = 18, Alpha-Cel C10, technical grade from International Fiber Europe NV.

[0244] The compositions reported in Table 1 were respectively fed to a co-rotating twin-screw extruder of the Icma San Giorgio MCM25HT model under the following operating conditions:

[0245] Screw diameter (D) = 25 mm;

[0246] L / D=52;

[0247] Speed ​​= 200 rpm;

[0248] Temperature distribution = 50-180-190 × 9–180-150 × 2 °C;

[0249] Throughput 10.1kg / h.

[0250] Table 1 - Composition

[0251]

[0252] The melt volume-flow rate (MVR) of the pellets obtained was measured at 190° C., 2.16 kg according to standard ISO 1133-1 (values ​​in Table 2).

[0253] The barrier properties were determined on films of 160-190 μm made with the compositions prepared according to Examples 1 to 7. The films were subjected to annealing at a temperature of 60-120° C. and with a residence time of 0.5-5 minutes.

[0254] The barrier properties were determined by permeation rate measurements carried out in an Extrasolution Multiperm permeometer at 23° C.-50% relative humidity according to standard ASTM F2622-08 for oxygen and according to standard ASTM F2476-05 for carbon dioxide, and by permeation rate measurements measured at a gradient of 23° C.-50% relative humidity according to standard ASTM E96 for water vapor (values ​​in Table 2).

[0255] The granules obtained were then injection molded into a mold cavity with a rectangular plate geometry (width=70 mm, length=80 mm, thickness=1 mm) on an Engel victory 120 model press using the following operating conditions for injection molding:

[0256] Injection temperature = 200°C

[0257] Oil power pressure = 70 bar

[0258] Filling time = 0.6s

[0259] Maintaining pressure = 500 bar

[0260] Hold time = 2s

[0261] Cooling time = 6s

[0262] Cycle time = 12s

[0263] Screw speed (RPM) = 90.

[0264] From these rectangular plates rods (length 30 mm, width 6 mm, thickness 1 mm) were obtained and then subjected to dynamic mechanical-torque analysis (DMTA) in torsion mode using an Ares G2 rotational rheometer from TA Instrument. The samples were heated from 25°C to 120°C at 3°C / min, with a deformation of 0.1% and a frequency of 1 Hz. The compositions were characterized at 70°C by the G' values ​​shown in Table 2 below.

[0265] Table 2 – Characterization

[0266]

[0267] The comminution test was carried out on samples with a length of 25 mm, a width of 25 mm and a thickness of 0.6 mm at 58° C. in controlled composting conditions according to standard ISO 20200:2004 “Plastics—Determinition of the degree of integration of plastic materials under simulated compositions conditions in a laboratory-scale test”. The compositions according to Examples 1 to 7 all showed a comminution weight loss of more than 90% within 90 days.

Claims

1. A biodegradable composition comprising, relative to the total amount of components i.-iv.: i) 20-60 wt. % of at least one biodegradable polyester; ii) 20-70% by weight of at least one biodegradable polymer other than the polyester i., selected from polyhydroxyalkanoates and / or aliphatic and / or aliphatic-aromatic diacid diol polyesters other than the polyester i., and mixtures thereof; iii) 0-50 wt. % of at least one filler; iv) 0-30 wt% vegetable fibers. The biodegradable polyester i. comprises: a) a dicarboxylic acid component, comprising, relative to the total dicarboxylic acid component: a1) 85 to 65 mol % of units derived from 2,5-furandicarboxylic acid or an ester thereof; a2) 15 to 35 mol % of units derived from at least one saturated dicarboxylic acid selected from adipic acid, azelaic acid, succinic acid, sebacic acid, brassylic acid or esters or derivatives thereof, preferably azelaic acid; a3) 0 to 15 mol % of units derived from at least one aliphatic saturated dicarboxylic acid which is not a saturated dicarboxylic acid in component a2 and is preferably selected from saturated C2-C 24 , C4-C is preferred 13 , more preferably C4-C 11 A dicarboxylic acid, or an ester thereof; a4) 0 to 5 mol % of units derived from at least one unsaturated aliphatic dicarboxylic acid or an ester thereof; b) a diol component, comprising, relative to the total diol component: b1) 95 to 100 mol % of units derived from 1,2-ethylene glycol; b2) 0 to 5 mol % of units derived from at least one saturated aliphatic diol other than 1,2-ethylene glycol; b3) 0 to 5 mol % of units derived from at least one unsaturated aliphatic diol.

2. A biodegradable composition comprising, relative to the total amount of components i.-iv.: i) 20-60% by weight of at least one biodegradable polyester i.; ii) 20-70% by weight of at least one polyhydroxyalkanoate; iii) 0-50 wt. % of at least one filler; iv) 0-30 wt% vegetable fibers.

3. A biodegradable composition comprising, relative to the total amount of components i.-iv.: i) 20-60% by weight of at least one biodegradable polyester i.; ii) 20 to 70% by weight of at least one aliphatic diacid diol polyester; iii) 0-50 wt. % of at least one filler; iv) 0-30 wt% vegetable fibers.

4. A biodegradable composition comprising, relative to the total amount of components i. to iv.: v) 20-60% by weight, preferably 25-55% by weight, more preferably 25-50% by weight of at least one biodegradable polyester i.; vi) 20 to 70% by weight, preferably 25 to 65% by weight, of at least one aliphatic-aromatic diacid diol polyester; vii) 0-50 wt %, preferably 3-45 wt %, more preferably 5-40 wt % of at least one filler; viii) 0-30 wt.% vegetable fibers.

5. The biodegradable composition according to any one of claims 1 to 4, characterized in that Less than 20 (cm 3 ×mm) / (m 2 × 24h × bar) against oxygen permeation barrier.

6. The biodegradable composition according to any one of claims 1 to 4, characterized in that Less than 45 (cm2) measured according to standard ASTM F2476-05 at 23°C-50% relative humidity 3 ×mm) / (m 2 × 24h × bar) against the permeation barrier of carbon dioxide.

7. The biodegradable composition according to any one of claims 1 to 4, characterized in that Less than 80 (g×30 μm) / (m 2 × 24h) permeation barrier against water vapor transmission.

8. The biodegradable composition according to any one of claims 1 to 4, characterized in that G' modulus values ​​higher than 40 MPa were obtained via dynamic mechanical-torque analysis at 70°C.

9. Films, fibers, nonwoven fabrics, sheets, molded, thermoformed, blown, expanded and laminated articles comprising the composition according to any one of claims 1 to 4.

10. Injection molded article comprising the composition according to any one of claims 1 to 4.

11. Injection moulded articles according to claim 10, suitable for preparing disposable cutlery, plates and cups, rigid containers, capsules for delivering beverages, preferably hot beverages, caps and lids, and food packaging which can be heated in conventional and microwave ovens.